Code of practice for selection, installation and maintenance of electrical apparatus for use in potentially explosive atmospheres (other than mining applications or explosive processing and manufacture). Installation and maintenance requirements for electrical apparatus with type of protection 'd'. Flameproof enclosure Part 3, (28th September 1979) - British Standards Institution
No abstract available